2022
DOI: 10.2337/dc22-1053
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Type 2 Diabetes and Mood, Anxiety, and Stress-Related Disorders: A Genetically Informative Register-Based Cohort Study

Abstract: OBJECTIVE To assess the association and familial coaggregation between early-onset type 2 diabetes (diagnosed before age 45 years) and mood, anxiety, and stress-related disorders and estimate the contribution of genetic and environmental factors to their co-occurrence. RESEARCH DESIGN AND METHODS This population-based cohort study included individuals born in Sweden during 1968–1998, from whom pairs of full siblings, half-sib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Our findings of stronger associations for first-than seconddegree relatives for MDD and anxiety disorders are in line with the findings of a Swedish familial co-aggregation study of early-onset T2DM and these disorders, where they similarly found a stronger association in full-siblings (sharing 50% of their segregating genes) than in cousins (sharing 25% of their segregating genes), the latter not reaching statistical significance for MDD (Liu et al, 2022). A Taiwanese study found that a family history of T2DM was correlated with a family history of major psychiatric disorders with ORs around 1.2 for schizophrenia, MDD, and bipolar disorder, but found no evidence of association between T2DM-PRS and these disorders (Su et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings of stronger associations for first-than seconddegree relatives for MDD and anxiety disorders are in line with the findings of a Swedish familial co-aggregation study of early-onset T2DM and these disorders, where they similarly found a stronger association in full-siblings (sharing 50% of their segregating genes) than in cousins (sharing 25% of their segregating genes), the latter not reaching statistical significance for MDD (Liu et al, 2022). A Taiwanese study found that a family history of T2DM was correlated with a family history of major psychiatric disorders with ORs around 1.2 for schizophrenia, MDD, and bipolar disorder, but found no evidence of association between T2DM-PRS and these disorders (Su et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Since GWAS-based genetic correlations do not always reflect phenotypic association patterns, using other genetically informative study designs, such as family designs, can help triangulate evidence of how genetic as well as environmental factors contribute to the associations between T2DM and psychiatric disorders. One recently published study showed an association between early-onset T2DM and mood, anxiety, and stress-related disorders within individuals and by investigating pairs of siblings and cousins (Liu et al, 2022). In addition to GWAS correlation and epidemiological familial risk studies, genetic cross-disorder association can be studied using polygenic risk scores (PRSs), which capture an individual's genetic risk for a specific condition by summarizing the effect of risk variants across the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health disorders including schizophrenia, bipolar affective disorder, and depression accounted for 38% of hospital bed‐days in the youngest age group 44 . Co‐occurrence of young‐onset type 2 diabetes and mental health disorders has been reported previously 45 , and reflects a shared lifestyle and other environmental factors, effects of psychotropic drugs on metabolic health, and challenges in coping with diabetes self‐management from an early age contributing to distress and other negative emotions.…”
Section: Health Burden Of Young‐onset Type 2 Diabetesmentioning
confidence: 89%
“…Notably, in another registry-based study, about 40% of hospitalizations among young individuals with T2DM were attributable to mental health issues[ 78 ]. In a study on Swedish people with young-onset T2DM, the risk of bipolar disorder, anxiety, depression or stress-related events was higher by up to 4-fold[ 79 ]. Among youth with T2DM, younger age at diagnosis was found to be an independent predictor for depression[ 80 ].…”
Section: Complications and Co-morbidities In Young-onset T2dmmentioning
confidence: 99%